2021
DOI: 10.5603/imh.2021.0035
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of Filipino seafarers and its implications for seafarers’ education

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“… 73 It is crucial to continue providing the aforementioned measures to further strengthen seafarers’ mental health and well-being. Abila and Acejo 74 highlight the importance of educating seafarers in the field of mental health, which would provide seafarers with useful information about mental health care, while Sampson and Ellis 75 provide a set of recommendations and measures for companies and relevant stakeholders aimed to improve seafarers’ mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“… 73 It is crucial to continue providing the aforementioned measures to further strengthen seafarers’ mental health and well-being. Abila and Acejo 74 highlight the importance of educating seafarers in the field of mental health, which would provide seafarers with useful information about mental health care, while Sampson and Ellis 75 provide a set of recommendations and measures for companies and relevant stakeholders aimed to improve seafarers’ mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular migrant workers, for example, may be more hesitant to register and sign up for Philippine aid for fear of disclosing their status. Those in the marine sector also faced great mental toll on top of the economic and health risks of the pandemic (Abila and Acejo, 2021), which may affect their capability and motivations in forming political remittances. Survey respondents were recruited through migrant organizations, some of which have been vocal critics of the Duterte administration and this may have some influence on the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has explored various risk factors affecting seafarers’ mental health, demonstrating that the working environment at sea exposes seafarers to stress and psychological harm ( Abila and Acejo, 2021 , Abila and Tang, 2014 , Iversen, 2012 , Jonglertmontree et al, 2022 , Sampson and Ellis, 2021 ). Nevertheless, due to the stigma associated with mental health problems, it is suggested that seafarers are reluctant to acknowledge them and seek support.…”
Section: Literature Reviewmentioning
confidence: 99%